Manajemen Kurikulum dalam Mengembangkan Mutu Pendidikan - Iwan Sopwandin; Randi Yusman; Ridwan Burhan Hak; Rudi Putra; Usman Alim (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
The curriculum is one of the indicators to measure the quality of an educational institution, because if the curriculum used is good then the targeted results will be achieved further to produce graduates who are outstanding and have good character. This study aims to analyze curriculum management at Al-Hidayah Cukangkawung Tasikmalaya Islamic High School. Qualitative methods were used in this study with a descriptive analysis approach. Data collection was used by observation techniques, interviews and documentation studies, while data analysis was carried out by means of data condensation, data presentation and conclusions. The results of this study indicate that Al-Hidayah Cukangkawung Islamic High School uses the 2013 curriculum and a typical curriculum which includes life skills education, tadarus and dhuha congregation, literacy, and field work practices (PKL). While the process of curriculum management at Al-Hidayah Islamic High School includes: 1) curriculum planning, initially a curriculum development team was formed and then the planning was divided into two levels, namely school-level curriculum planning and class-level curriculum planning; 2) the implementation of the curriculum, the implementation of the curriculum is under the supervision and responsibility of the school principal who is accompanied by the vice principal in the field of curriculum; and 3) curriculum evaluation, this activity is carried out at the end of the year in the form of an end of school year evaluation meeting.